Service Orientation in Holonic and Multi-Agent Manufacturing Proceedings of SOHOMA 2018 - Borangiu, Theodor; Trentesaux, Damien; Thomas, André; Cavalieri, Sergio (Studies in Computational Intelligence, 2019)
XVIII, 462 p. 160 illus., 124 illus. in color.